Mikrohabitat Tumbuhan Endemik Cyrtandra Polyneura Di Hutan Gandang Dewata untuk Budidaya Berbasis Agroforestri (Microhabitat of the Endemic Plant Cyrtandra polyneura in the Gandang Dewata Forest for Agroforestry-Based Cultivation) - Wahyullah Wahyullah; Nurmuliayanti Muis; A. Baso Manguntungi; Irlan Irlan; Andi Asikin Muchtar; Ummu Kulsum (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2025)
The Sandaniki plant (Cyrtandra polyneura) is an endemic species found in the Gandang Dewata Forest in West Sulawesi. It is traditionally used as a food source during ceremonies of the Mamasa tribe. Excessive exploitation in its natural habitat raises concerns regarding its sustainability. This study aimed to identify microhabitat characteristics and analyze the relationship between environmental factors and the C. polyneura growth. The information will be use as baseline information to support its cultivation on community-owned land with an agroforestry system. Data were collected through direct field observations in 25 plots in the Gandang Dewata Forest. The observed parameters included the population of C. polyneura as the dependent variable; and soil moisture, light intensity, soil pH, and canopy cover density as the independent variables. The obtained data were analyzed quantitatively using descriptive methods and Spearman’s Rho correlation analysis in SPSS. The results showed a strong positive correlation between soil moisture, tree density, and the population of C. polyneura. These findings suggest that C. polyneura can be cultivated in an agroforestry system under moist, shady, and densely forested microhabitat conditions, and slightly acidic soil. This study recommends adaptive cultivation as a conservation strategy and an agroforestry-based local food revitalization, in line with the wisdom of the Mamasa tribe.